Pengembangan Alat Evaluasi Menggunakan Aplikasi Ujon pada Pembelajaran Bahasa Indonesia di MTs - Purnawati, Lilik; Nugrahani, Farida; Sudiyana, Benedictus (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
This research aims to develop an evaluation tool using the Ujon application in Indonesian learning in MTs. This research uses the Research and Development (R&D) method with a development research model from Borg and Gall. Research instruments use tests and questionnaires. The results showed that the evaluation tool product using the Ujon application in the form of HOTS multiple-choice questions was 23 valid questions. The validation of media experts showed a final percentage score of 93% with very valid criteria while material experts a final presentation score of 94.66% with very feasible criteria. The evaluation tool that was tested on a large scale using the Ujon application showed a final presentation score of 83.1% with practical criteria, student responses based on the percentage questionnaire of 87.13% including very interesting criteria and responses from teachers to the evaluation tool that was tested 100% including very practical criteria. In conclusion, the evaluation tool developed using the Ujon application is declared very feasible, valid, and practical to use in learning evaluation and interesting for students.